NONLINEAR DYNAMICS OF SPECIFIC DNA-PROTEIN INTERACTION - DWIPUTRA (NIM : 20214008), DONNY
Interactions between DNA binding protein and specific base pairs of nucleic acid is critical for biological processes. We propose a new model of DNA-protein interactions to depict the dynamics of specific DNA-protein interactions. Hydrogen bonds (H-bonds) are, among the other intermolecular interactions in DNA, the most distinctive in term of specificity of molecular bonds. As H-bonds account for specificity, we only consider the dynamics affected by H-bonds between DNA base pairs and H-bonds connecting protein side chains and DNA. The H-bonds are modeled by Morse potentials and coupling terms in the Hamiltonian of coupled oscillators resembling a coupling between planar DNA chain and a protein molecule. In this paper we give a perturbative approach as an attempt for a soliton solution. The solution is in the form of nonlinear travelling wave having the amplitudes satisfying coupled nonlinear SchrÃ‚Â¨odinger equations and is interpreted as the mediator for nonlocal transmittance of biological information in DNA.